IMPLEMENTASI MEDIA PEMBELAJARAN SECRET BOX - Jenita Anjani Br Sembiring (Universitas Quality, 2022)
The nation's intellectual life may be realized via education, which is a tool that is significant for all spheres of society. All pupils must be taught the same material using tactics or procedures that are effective in the educational process. In line with the subjects covered in the classroom, educators can also make use of a variety of learning media. It is believed that using learning resources would improve how effectively pupils understand the material. One of the learning tools that will be utilized in this research is the Secret box. The following are the goals of this study: (1) Fostering students' creativity and curiosity for artifacts created in line with the study topic. (2) Foster a greater sense of cooperation among students when they work in groups. The data processing methods were discovered through field research and helpful conversations with associated parties.